Eksplorasi Imunoterapi dan Terapi Gen dalam Pengobatan Tumor Otak: Literature Review - Hana Muthi'a Putri; Windarti, Indri; Mayasari, Diana; Susianti, Susianti (Medula, 2024)
Brain tumors are a significant neurological disorder with a high mortality rate, especially in cases of glioblastoma, which is highly aggressive and difficult to treat. Conventional treatment methods, such as surgery, radiation therapy, and chemotherapy, are often not effective enough, particularly in advanced stages. This study aims to explore two innovative approaches, namely immunotherapy and gene therapy, as alternative treatments for brain tumors. Immunotherapy works by enhancing the immune system's ability to fight cancer cells through methods such as checkpoint inhibitors, cancer vaccines, and CAR-T therapy. However, the success of immunotherapy is often hindered by the blood-brain barrier (BBB), which limits the delivery of therapy to the brain. On the other hand, gene therapy offers a solution by modifying genetic material, either to repair damaged genes or to directly destroy cancer cells. Approaches such as the use of oncolytic viruses, CRISPR technology, and nanoparticles have shown promising results in preclinical research and early clinical trials, particularly for glioblastoma. The combination of immunotherapy and gene therapy opens new opportunities to enhance treatment effectiveness by strengthening the immune response and targeting tumors more specifically. However, challenges remain, including treatment resistance, side effects, and limitations in brain delivery methods. Further research is needed to ensure the safety, efficacy, and widespread application of this combination therapy. Immunotherapy and gene therapy have great potential as breakthroughs in the future treatment of brain tumors. Relevant literature, including articles and journals from both national and international sources, were gathered through online searches in various databases, such as Google Scholar, PubMed, and NCBI, and used to compile this article.